Effects of three nudging conditions (funny labelling, visual priming, and default option) on choice and intake of snack vegetables in school children - Vogt, Marie; Olsen, Annemarie (Science Talks (Online), 2024)
This study aimed at comparing effects of three nudging strategies on choice and intake of vegetables in children. A total of 82 children, 10–13 years old, participated during their habitual snack break at school. The study was a within-subject intervention using a snack buffet setting with ten different foods focusing on three vegetables. The experimental conditions were visual priming (green tablecloth), default option (pre-portioned vegetable containers), funny labelling (attractive vegetable names), and a control (neutral setting). Each child's choice, intake and waste of each food were determined by taking pictures before and after sessions. Choice of vegetables was significantly higher in the default option compared to the other nudging conditions (p < 0.001). The default option resulted in a higher vegetable intake than the control (p = 0.012) and visual priming (p = 0.001). The default option had the highest variety of vegetables taken and eaten, but also resulted in the most food waste. No significant differences were found for vegetable choice and intake between the control, visual priming, and labelling. In conclusion, this study demonstrated that using default options in the form of pre-portioned vegetable containers successfully increased vegetable choice, and intake, whereas priming and labelling had no effects.